2018
DOI: 10.1002/ped4.12037
|View full text |Cite
|
Sign up to set email alerts
|

Serotypes of human enteroviruses causing pediatric viral encephalitis and meningitis in Hebei province, China, from 2013 to 2015

Abstract: Importance: Viral encephalitis and meningitis are severe infectious diseases responsible for substantial morbidity and mortality in children. Enteroviruses are typically the most common causative agents of viral encephalitis and meningitis. Objective: This study aimed to investigate the etiology of viral encephalitis and meningitis among children in Hebei province, China. Methods: Cerebrospinal fluid samples from children with viral encephalitis (n=309) and meningitis (n=133) were collected between Nov 2013 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 32 publications
1
4
0
Order By: Relevance
“…In our research, mNGS was used to study the epidemiology of VE and/or VM in Zhejiang Province in 2021. Similar to the results of previous studies (Chen et al, 2018;Sun et al, 2019), our data showed that HEV remains the primary pathogen of pediatric VE and/or VM based on the evidence that 28% (14 of 50) of CSF samples of all enrolled patients in Zhejiang Province in China were HEV-positive. Moreover, Echo 18 replaced Echo 30 as the most frequent serotype.…”
Section: Discussionsupporting
confidence: 90%
“…In our research, mNGS was used to study the epidemiology of VE and/or VM in Zhejiang Province in 2021. Similar to the results of previous studies (Chen et al, 2018;Sun et al, 2019), our data showed that HEV remains the primary pathogen of pediatric VE and/or VM based on the evidence that 28% (14 of 50) of CSF samples of all enrolled patients in Zhejiang Province in China were HEV-positive. Moreover, Echo 18 replaced Echo 30 as the most frequent serotype.…”
Section: Discussionsupporting
confidence: 90%
“…An outbreak of E18-associated AM in Taiwan in 2006 was reported, and E18 accounted for 27.4% of the total EV-positive cases ( 13 ). We previously reported an E18-associated outbreak of encephalitis/meningitis in children in Hebei Province in China ( 12 , 21 ). In our analysis, E18 was the main pathogen associated with VE/AM in children in 2015, accounting for 74.4% of all enteroviruses detected in children with VE/AM CSF specimens.…”
Section: Introductionmentioning
confidence: 99%
“…The main pathogens responsible for viral meningitis vary by geographical region, season, and detection methodology. [5] In England and Wales, the most common causative agents of viral meningitis were enteroviruses (EVs), herpes simplex virus (HSV) and varicella zoster virus (VZV). In America, Leber, et al reported that the most common causative agents of VE and VM were enteroviruses and human herpesvirus [6].…”
Section: Introductionmentioning
confidence: 99%
“…In America, Leber, et al reported that the most common causative agents of VE and VM were enteroviruses and human herpesvirus [6]. In Australia, the most common causative agents were HSV and VZV, while Japanese encephalitis virus was the most common causative agent of VE among children in southern Vietnam [5].…”
Section: Introductionmentioning
confidence: 99%